Buletin Peternakan : ELEMEN KLASTER INDUSTRI PENGOLAHAN SUSU DI DAERAH ISTIMEWA YOGYAKARTA - Nur Laili Marufah, Tri Djoko Wisnumurti, Budi Guntoro (Peternakan UGM, 2015)
This research was conducted to study the elements and value chain of milk-processing clusterÂ industry in Daerah Istimewa Yogyakarta. The respondent in this study consisted of cow and goats milkÂ processing industry, dairy cooperative and related institution. The data consisted of primary data andÂ secondary data. Primary data were collected through observation and interviews, while secondary dataÂ obtained from statistical data from Department of Industry, Trade and Cooperatives, Agricultural ServiceÂ of Agriculture Department and LPPOM MUI DIY.